High contamination of Salmonella spp. in raw milk in Ecuador: molecular identification of Salmonella enterica serovars Typhi, Paratyphi, Enteritidis and Typhimurium - Anthony Loor-Giler; Anthony Loor-Giler; Camila Sanchez-Castro; Marcela Robayo-Chico; Byron Puga-Torres; Silvana Santander-Parra; Luis Nuñez; Luis Nuñez (Frontiers in Sustainable Food Systems)
In Ecuador, the consumption of raw milk is fundamental, nonetheless it also presents risks due to the presence of Salmonella, a pathogen responsible for foodborne diseases (FBD). This study evaluated the prevalence of Salmonella spp. in raw milk from the provinces of Pichincha and Manabí, identifying the Salmonella enterica serovars Typhi, Paratyphi, Enteritidis and Typhimurium, in order to determine the risks associated with FBD. For this study, 600 raw milk samples were analyzed using a specific qPCR assay for Salmonella enterica, in parallel, bacterial isolation of the strains was performed according to ISO 6579-1:2017, and serotyped using endpoint PCR assays. Finally, the 16S rDNA of some isolates was sequenced and the identification of these isolates was confirmed. A prevalence of 37.5% (n = 225 positive samples) was obtained, where the climatic season had a significant influence on Salmonella enterica contamination, being higher in the warm season. In the analysis of serovars, Salmonella Typhimurium and Salmonella Enteritidis predominated with 62 and 60 samples respectively, followed by Salmonella Paratyphi with 32 samples and Salmonella Typhi with only 28 samples. A phylogenetic relationship was found between the 16 s samples sequences of this study and those previously reported in NCBI. The high prevalence of Salmonella enterica in raw milk intended for consumption in Ecuador represents a significant public health risk due to its high pathogenic potential. It is therefore essential to improve biosafety practices among livestock producers and implement sanitary control measures to reduce the risk posed by this pathogen in raw milk and similar food products.